Cellular RNA Helicase p68 Relocalization and Interaction with the Hepatitis C Virus (HCV) NS5B Protein and the Potential Role of p68 in HCV RNA Replication - Goh, Phuay-Yee (American Society for Microbiology, 2004)
Chronic infection by hepatitis C virus (HCV) can lead to severe hepatitis and cirrhosis and is closely associated with hepatocellular carcinoma. The replication cycle of HCV is poorly understood but is likely to involve interaction with host factors. In this report, we show that NS5B, the HCV RNA-dependent RNA polymerase (RdRp), interacts with a human RNA helicase, p68. Transient expression of NS5B alone, as well as the stable expression of all the nonstructural proteins in a HCV replicon-bearing cell line (V. Lohmann, F. Korner, J.-O. Koch, U. Herian, L. Theilmann, and R. Bartenschlager, Science 285:110-113), causes the redistribution of endogenous p68 from the nucleus to the cytoplasm. Deletion of the C-terminal two-thirds of NS5B (NS5BΔC) dramatically reduces its coimmunoprecipitation (co-IP) with endogenous p68, while the deletion of the N-terminal region (NS5BΔN1 and NS5BΔN2) does not affect its interaction with p68. In consistency with the co-IP results, NS5BΔC does not cause the relocalization of p68 whereas NS5BΔN1 does. With a replicon cell line, we were not able to detect a change in positive- and negative-strand synthesis when p68 levels were reduced using small interfering RNA (siRNA). In cells transiently transfected with a full-length HCV construct, however, the depletion (using specific p68 siRNA) of endogenous p68 correlated with a reduction in the transcription of negative-strand from positive-strand HCV RNA. Overexpression of NS5B and NS5BΔN1, but not that of NS5BΔC, causes a reduction in the negative-strand synthesis, indicating that overexpressed NS5B and NS5BΔN1 sequesters p68 from the replication complexes (thus reducing their replication activity levels). Identification of p68 as a cellular factor involved in HCV replication, at least for cells transiently transfected with a HCV expression construct, is a step towards understanding HCV replication.